Composite of graphene oxide impregnated palm kernel shell based activated carbon for dye wastewater treatment / Tan Yan Ying - Tan , Yan Ying (2025)
Dye wastewater generated from various industrial processes can lead to substantial pollution and environmental damage due to its persistent and recalcitrant nature. Among the various wastewater treatment technologies, adsorption using green and low-cost biomass-based materials stands out as a promising approach for treating dye wastewater. However, raw biomass-based adsorbents such as palm kernel shell (PKS), rubber seed shell, and coconut shell often have limitations in selectivity, recovery, and adsorption capacity, which restrict their use in treating different types of wastewater. This study aims to enhance the adsorption performance of raw PKS activated carbon (PKSAC) through the impregnation with graphene oxide (GO) and iron oxide. Physicochemical analyses revealed that after impregnation with GO and iron oxide, the ternary composite exhibited a significant increase in oxygen content (from 6.01% to 49.73%), a larger pore width (from 3.00 nm to 9.99 nm), and increased oxygenated functional groups compared to raw PKSAC. The adsorption performance of PKSAC-based adsorbents was evaluated for treating synthetic wastewater containing an anionic dye. The adsorption study demonstrated that the ternary composite performed better, achieving 99.8% color removal efficiency and an adsorption capacity of 27.3 mg/g, compared to other PKSAC-based adsorbents (60.7%-73.1%; 16.6 mg/g-19.9 mg/g) under optimum conditions. The ternary composite showed superior performance in chemical oxygen demand and color removal efficiencies, surpassing commercial activated carbons (CACs) by 28.4% and 31.9%, respectively. The reusability of the composite was confirmed over five cycles, maintaining 74.1% performance, significantly higher than CACs (30.0%). Furthermore, the iron leaching (<0.3 mg/L) was negligible for drinking water, confirming the stability and safety of the composite. To further improve adsorption performance, the synthesis process of the ternary composite was optimized. This optimized ternary composite demonstrated an adsorption capacity of 76.4 mg/g for actual industrial printing wastewater, which was 34.5% higher than the composite before optimization (56.8 mg/g). Experimental results indicated that adsorption using the ternary composite is predominantly a monolayer chemisorption process. A quantum chemical analysis revealed adsorption energies below -50 kJ/mol for all functional groups. Feature importance analysis using machine learning revealed that the chemical properties of the adsorbents had a more significant impact on adsorption performance than physical properties. This study also evaluated the possibility of using the spent adsorbent in brick formation, in addition to conducting leaching and phytotoxicity studies. In summary, the research proved that the ternary composite developed from PKSAC is an efficient adsorbent for treating dye wastewater, offering enhanced performance, stability, and practicality for industrial applications.